Synergistic effect approaching record-high figure of merit in the shear exfoliated n-type Bi2O2-2xTe2xSe. (March 2020) - Pan, Lin; Liu, Wei-Di; Zhang, Jie-Yun; Shi, Xiao-Lei; Gao, Han; Liu, Qing-feng; Shen, Xiaodong; Lu, Chunhua; Wang, Yi-Feng; Chen, Zhi-Gang
Abstract: Due to the nature of high stability and eco-friendliness, layered n-type Bi2 O2 Se-based thermoelectric materials have attracted extensive research interest. In order to reduce lattice thermal conductivity and enhance thermoelectric performance of Bi2 O2 Se-based thermoelectric materials, here, we introduced Te substitution at O site into Bi2 O2-2x Te2x Se prepared by a shear exfoliation method. The induced high-density nanosized Bi2 O2 Se grains and point defects can effectively scatter both mid and short-wavelength phonons, leading to a low lattice thermal conductivity of ~0.57 W m −1  K −1 at ~773 K. Furthermore, Se vacancies generated by the shear exfoliation induced a high carrier concentration approaching the optimized level, and in turn lead to relatively high electrical performance. The synergistic high electrical performance and low lattice thermal conductivity secured a record-high dimensionless figure of merit, zT, of ~0.69 at ~773 K. This study indicates that shear exfoliation method and Te substitution are promising methods to optimize the thermoelectric properties of Bi2 O2 Se-based thermoelectric materials. Graphical abstract: With high stability, low-cost and eco-friendliness, n-type Bi2 O2 Se attracted increasing interest. Here, we discovered hierarchical structure of nano-grians, point defects, impurity interfaces in shear exfolicated Bi2 O2-2x Te2x Se can effectively scatter phonons leading to low lattice thermal conductivity of ~0.57 W m −1  K −1 . With synergistically optimized electron concentration deriving from shear exfolication induced Se vacancies, the figure of merit increased to ~0.69. Image 1 Highlights: Nano-grains, point defects and interfaces scatter phonons at a wide frequency range. Approaching low lattice thermal conductivity of ~0.57 W m −1  K −1 . Shear exfoliation induced additional Se vacancies secured optimized carrier concentration. A record-high figure of merit, zT, of 0.69 in Bi2 O2 Se-based thermoelectric materials.